The sense of humor: beyond laughter - Quezada Zevallos, Jenny Zarela (2015)
The authors make a brief review of the evolution of the humor concept, the emotional, cognitive and physiological processes, the explanatory theories about the humor, the development of the sense of humor and laughter, as well as the evaluation of the sense of humor and laughter in Psychotherapy, concluding with recent researches about the sense of humor.